Effect of irrigation intervals on growth and chemical composition of some Curcuma spp. plants - MAKARIM A. MOHAMED; HEND E. WAHBA; MOHMED E. IBRAHIM; ABD-ELGHANI A. YOUSEF (Smujo International, 2014)
Abstract. Mohamed MA, Wahba HE, Ibrahim ME, Yousef AA. 2014. Effect of irrigation intervals on growth and chemical composition of some Curcuma spp. plants. Nusantara Bioscience 6: 140-145. The Influence of irrigation intervals on the growth, yield of rhizomes and chemical composition of both Curcuma aromatica and Curcuma domestica plants was investigated. Three irrigation treatments were used in this experiment. The first treatment was irrigated every one week. The second and third treatments were irrigated every two and three weeks. The long irrigation intervals significantly reduced growth parameters and chemical composition. Growth parameters, i.e. plant height, number of leaves, width of the leaf, fresh and dry weight of rhizomes, as well as chemical composition, i.e. total carbohydrate, volatile oil and curcumin in dry rhizomes increased when the plants irrigated every week compared to irrigation treatments every two or three weeks. Also, C. aromatica gave the higher values of growth parameter and chemical composition compared to C. domestica under all irrigation treatments.